Analisis Respon Siswa Terhadap Virtual Laboratory Berbasis Adobe Animate Pada Pokok Bahasan Materi Usaha dan Energi - Tika Widiya Ningrum; Maryani .; Nanda Salsabila Ayu Prasetya; Anisa Septi Pratiwi; Vandaria Dewi Cahyani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Learning is an interaction between students and teachers supported by learning materials. Physics is a subject that is considered abstract and difficult for students. Virtual laboratory is an alternative to animate teaching and learning activities. The research method used is Research and Development with the design of learning media using the 4D model. Data collection was carried out at SMAN 3 Jember with a sample of 30 students. Based on the final results of student responses, an average score of 87.5% was obtained which stated that the development of adobe animate-based virtual laboratory media was included in the very good criteria. Virtual laboratory media based on Adobe Animate can help students understand material, especially in abstract learning such as physics material. Based on one of the questions in the questionnaire, it also states that virtual laboratory media based on Adobe Animate can also encourage student learning motivation. Based on the results of student responses, it can be concluded that the adobe animate-based virtual laboratory that has been developed obtains student responses with very good criteria Kata Kunci: Virtual laboratory, Adobe Animate, Usaha dan Energi